The chemical composition and the preservative, antimicrobial, and antioxidant effects of Thymus broussonetii Boiss. essential oil: an in vitro and in silico approach - Boukhira, Smahane; Amrati, Fatima Ez-Zahra; Chebaibi, Mohamed; Grafov, Andriy; Mothana, Ramzi A.; Al-Yousef, Hanan M.; Bousta, Dalila (Frontiers in Chemistry, 2024)
The aim of this study was to evaluate the antioxidant, antimicrobial, and preservative efficacy of Thymus broussonetii Boiss. essential oil (EO) in topically applied formulation using a challenge test. The antioxidant effect of the EO was evaluated using three methods, the DPPH, β-carotene linoleic acid, and the FRAP methods. The antimicrobial activity and the minimum inhibitory concentration (MIC) of this EO were assayed by the disk-diffusion method and the broth microdilution method, respectively. The preservative efficacy of T. broussonetii EO was assayed at 1% and 2% (v/w) in topical cream formulation using a challenge test against standard specific microorganisms recommended by the European Pharmacopoeia. Furthermore, the identified phytochemical compounds were docked for their effect on nicotinamide adenine dinucleotide phosphate oxidase, human casein kinase 1 alpha 1 (CSNK1A1), Glycogen synthase kinase 3.Results and discussion: Chemical composition of the EO revealed the presence of thymol (63.09%), p-cymene (11%) and γ-terpinene (8.99%) as the major components. The antioxidant assays revealed that the essential oil exhibited strong antioxidant activity as indicated by the minimum inhibitory concentration IC50. The investigated essential oil exhibited an important antimicrobial activity against all tested microorganisms, the MICs of EO against bacteria and fungi were 0.02 -1%. Moreover, the EO of T. broussonetii evaluated at 2% (v/w) in cream formulation succeeded in satisfying the A criteria for preservation efficacy against Staphylococcus aureus, Escherichia coli and Aspergillus brasiliensis but exhibited less efficacy against Pseudomonas aeruginosa (1.78 log reduction in the number of CFU/g after the 7 day of evaluation) and Candida albicans (1.09 log reduction in the number of CFU/g after the 14 days of evaluation) when compared to the synthetic preservative Phenoxyethanol 1% (v/w). In silico results showed that the antimicrobial activity of T. broussonetii EO is mostly attributed to thymol, terpinene-4-ol, and aromadendrene, while antioxidant activity is attributed to thymol.These results indicate that the EO of T. broussonetii possess an important antimicrobial and antioxidant activities and can therefore be used as a natural preservative ingredient in cosmetic industry.